Analysis of Mathematical Thinking Skills on Numerical Problems - Ferry Ferdianto; Siti Latifah; Yohanes Leonardus Sukestiyarno (Universitas Negeri Semarang, 2022)
Abstract. This study aims to determine students' mathematical thinking skills on numeracy problems. The research method used is the descriptive qualitative method, with the subjects in this study being class VIII G students, totaling 20 students with even absent numbers. The instrument used in data collection used a numeracy test instrument using indicators of mathematical thinking ability from Stacey and interviews. Data analysis techniques used include data reduction, data presentation, and conclusion. The results showed the results of the analysis of the percentage of overall indicators, and the analysis of per indicator for each question of mathematical thinking ability 20 students with even-numbered absences in class VIII G was in the medium category, with an overall average of 33%.